The Risk Screener Violence (RS-V): retrospective prediction of violent and aggressive incidents within the prison setting - Smeekens, Marjam V.; De Vries Robbé, Michiel; Popma, Arne; Kempes, Maaike M. (Frontiers in Psychology, 2024)
Physical and verbal violence towards staff or other detained individuals is a reoccurring problem within correctional facilities. Screening for violence risk within the prison setting could provide a valuable first step in the prevention of institutional violence. The brief and compact Risk Screener Violence (RS-V) has shown to be an efficient new method for assessing concerns regarding post-release violent offending for incarcerated persons. This study aimed to find out whether the RS-V is also able to predict future violent and aggressive incidents during imprisonment. The predictive validity of the RS-V for future violent and aggressive incidents during a follow-up time of four months within prison was analyzed, using a file-based design. Violent incidents towards staff and other inmates (physical violence and violent threats), other aggressive incidents (aggression towards objects and verbal disruptive behavior), and both categories combined, were included as outcome measures based on disciplinary reports. The RS-V showed medium to large predictive values for both violent and aggressive behavior during prison stay. In particular, good predictive values of the RS-V were found for violence towards prison staff. This study shows that, besides post-release violent recidivism, the RS-V is able to accurately predict future violent and aggressive incidents during prison stay. By correctly differentiating between low concern and high concern individuals, the RS-V aims to contribute to more personalized interventions and risk management and, subsequently, to improved prison safety. Future studies using prospective prison practice data are needed to further support the validity of the RS-V regarding institutional violence.